2015
DOI: 10.1007/s00415-015-7692-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the multimodal assessment of capacities in severe dementia: a novel cognitive and functional scale for use in severe dementia

Abstract: The multimodal assessment of capacities in severe dementia (MAC-SD), a novel cognitive and functional assessment, was developed for use with patients with severe dementia. Its psychometric attributes were examined in a unicenter, open, observational study. The MAC-SD along with the Spanish language Severe Mini Mental Exam were administered to 103 patients with a diagnosis of severe dementia. Psychometric analyses were performed to determine acceptability, reliability, validity, and responsiveness. As a whole, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The SIB, for instance, has proven to be a poor indicator of cognitive state, and especially of change in cognitive state, in the last stages of dementia; both the SIB and the SMMSE boast significant floor effects not seen in the MAC-SD, especially in populations with low levels of education [ 30, 31 ]. The Spanish version of the MAC-SD showed no floor effects despite the overall low level of education of the participant pool [ 6 ], indicating that it is an appropriate measure regardless of participant education level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SIB, for instance, has proven to be a poor indicator of cognitive state, and especially of change in cognitive state, in the last stages of dementia; both the SIB and the SMMSE boast significant floor effects not seen in the MAC-SD, especially in populations with low levels of education [ 30, 31 ]. The Spanish version of the MAC-SD showed no floor effects despite the overall low level of education of the participant pool [ 6 ], indicating that it is an appropriate measure regardless of participant education level.…”
Section: Discussionmentioning
confidence: 99%
“…The MAC-SD is a Spanish and English language psychometric tool to measure cognition and functioning in patients with severe dementia. The Spanish language version proved to be reliable, valid, and useful in the care and treatment of patients with severe dementia [ 6 ]. This study investigates the same parameters in the English language version of the MAC-SD with a United States cohort.…”
Section: Introductionmentioning
confidence: 99%
“…The SEM was calculated with the standard deviation (SD) formula: where ICC represents the test-retest reliability coefficient. An acceptable SEM score was defined as less than half the baseline SD [ 8 ]. The MDC, which is the threshold for determining clinical changes beyond measurement error, was calculated with the following formula: 1.96 Terwee et al [ 15 ] suggested that 50 samples were needed to examine test-retest reliability to increase reproducibility.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the clinical utility of the CTSD was evaluated, showing generally good validity and reliability [ 7 ]. However, in recent years, the methodological quality of studies aiming to develop outcome measures has been questioned [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation